Another throat : twenty-first-century Black US persona poetry and the archive - Sharp, Ryan (The University of North Carolina Press, 2024)
The early twenty-first century has seen a sharp rise in Black US poets employing the mask of persona, often including and interrogating archival materials as they do so. While some have observed this rise and noted its connection to historical figures, Ryan Sharp explores it more deeply, as a project-based historical and poetic practice. Sharp examines its sustained use of historical persona and capacity for conjuring Black speakers as a countermeasure against the archival silencing and misrepresentation of Black voices and histories--a tactic he theorizes as poetic fabulation--through the poetry of Elizabeth Alexander, Cornelius Eady, Adrian Matejka, Patricia Smith, Natasha Trethewey, and Frank X Walker. This poetic practice is not only about looking back but about critically and creatively (re)imagining the past to expand the possibilities for Black presents and futures. Through his argument, Sharp demonstrates how the unique aesthetic and rhetorical license afforded to poetry, along with the interiority of persona, empowers such historically minded projects to be concurrently invested in the curation of Black narratives and identities.
Keywords: American poetry -- African American authors -- History and criticism.; American poetry -- 21st century -- History and criticism.; Persona (Literature); African Americans -- Archives -- History.; Poésie américaine -- Auteurs noirs américains -- Histoire et critique.; Persona (Littérature); African American.; Poetry.; LITERARY CRITICISM.; African American Studies.; Ethnic Studies.; SOCIAL SCIENCE.; American.; POETRY.; Electronic books.; Literary criticism.; Critiques littéraires.